2020
DOI: 10.1136/bmjopen-2018-026345
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy compared with standard moist wound care on diabetic foot ulcers in real-life clinical practice: results of the German DiaFu-RCT

Abstract: ObjectivesThe aim of the DiaFu study was to evaluate effectiveness and safety of negative pressure wound therapy (NPWT) in patients with diabetic foot wounds in clinical practice.DesignIn this controlled clinical superiority trial with blinded outcome assessment patients were randomised in a 1:1 ratio stratified by study site and ulcer severity grade using a web-based-tool.SettingThis German national study was conducted in 40 surgical and internal medicine inpatient and outpatient facilities specialised in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 27 publications
1
60
0
6
Order By: Relevance
“…Approximately 15% of people suffering from diabetes have diabetic ulcer during their lifetime, and 85% of amputations in diabetic patients are caused by foot ulceration, which further deteriorates to severe infection. Besides, 50%–70% of all lower limb amputations performed are the result of diabetes 52,53 …”
Section: Chronic Wound Characteristics and Clinical Needmentioning
confidence: 99%
“…Approximately 15% of people suffering from diabetes have diabetic ulcer during their lifetime, and 85% of amputations in diabetic patients are caused by foot ulceration, which further deteriorates to severe infection. Besides, 50%–70% of all lower limb amputations performed are the result of diabetes 52,53 …”
Section: Chronic Wound Characteristics and Clinical Needmentioning
confidence: 99%
“…100 A very recently published multicenter RCT concluded that NPWT was not superior to standard moist wound care in wound closure rate or time to complete closure. 101 Nevertheless, there is a weak recommendation for the use of NPWT in addition to standard of care for the management of patients with diabetes and postoperative wounds. 5,102…”
Section: Adjunct Therapiesmentioning
confidence: 99%
“…Luka kronis sering terjadi pada penderita diabetes mellitus karena adanya gangguan dalam mekanisme penyembuhan luka. Luka pada pasien DM tersebut akan memiliki dampak besar terhadap morbiditas, mortalitas dan kualitas hidup pasien DM (Seidel et al, 2020).…”
Section: Pendahuluanunclassified
“…Sekitar 15% dari pasien DM mengalami komplikasi berupa luka pada kaki selama hidup mereka (Seidel et al, 2020). Apabila penanganan luka ini dilakukan secara terlambat maka akan memperburuk keadaan dan akan mengakibatkan jaringan di sekitar luka menjadi mati, dan harus dilakukan amputasi (Santoso, 2017).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation